EVALUATION OF ANTIBACTERIAL PROPERTIES OF ESSENTIAL OILS FROM CLOVE AND EUCALYPTUS - Sharma, Suman; Singh, Stuti; Bond, James; Singh, Apekshita; Rustagi, Anjana (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â Â Objective: To substantiate the data for naturally available sources of antibacterial and bactericidal agents, this study was undertaken. The specific aim was to analyze antibacterial properties of two essential oils from clove (Eugenia caryophyllata) and Eucalyptus (Eucalyptus globulus) against Sphingobium indicum, Escherichia coli (Gram-negative bacteria) and Staphylococcus aureus, Bacillus subtilis (Gram-positive bacteria), which are clinically significant strains. Methods: The analysis was performed by measuring the zone of inhibition or haloâ€ using disk diffusion method. Results: Out of two oils used, clove oil was found to be more effective in inhibiting growth of all the four types of bacterial strains used in the study. B. subtilis was the most susceptible bacterial strain to clove oil showing maximum area of 7.54 cm2 for the halo/zone of inhibition, whereas E. coli was the least susceptible with 5.14 cm2 area of the halo. Eucalyptus oil inhibited growth in S. indicum and E. coli but the area of inhibition zone was much less in comparison to clove oil. Staphylococcus and Bacillus strains were found completely insensitive to eucalyptus oil. Conclusion: New antibacterial agents are very valuable in multidrug-resistant bacteria and the present study provides additional support to the already available data to use essential oils against various strains of bacteria. The clove oil proved more suitable as antibacterial agent than eucalyptus oil. Keywords: Essential oils, Antibacterial properties, Disk diffusion